If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -105 = -15y Solving -105 = -15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15y' to each side of the equation. -105 + 15y = -15y + 15y Combine like terms: -15y + 15y = 0 -105 + 15y = 0 Add '105' to each side of the equation. -105 + 105 + 15y = 0 + 105 Combine like terms: -105 + 105 = 0 0 + 15y = 0 + 105 15y = 0 + 105 Combine like terms: 0 + 105 = 105 15y = 105 Divide each side by '15'. y = 7 Simplifying y = 7
| 24m^2+18-15= | | 3a+4a-10=11 | | -2m=-10 | | n+5n=72 | | 2x^2+2-14x=90 | | z+3+7=4+7 | | 3x-4=50 | | 12h-17-h+16-2h= | | x^3-4x^2+4x-3=0 | | z(2z+7)=4 | | -3z+6+4z=13 | | 9x-18x=63 | | 2x^2-33=0 | | 2x+25=7x+5 | | 21-7y=10y-1.89 | | 48h^2-86h+35= | | -6z+2+9z=17 | | -5=5t-5 | | 2+2+2+2*0+2= | | -5=-5-5 | | 96d^2-76d-77= | | 20+x=4x | | 6x^2+67x-60=0 | | x^2+11x-30=0 | | m^2=196 | | 3-2(b-1)=b-10 | | 4(t-4)+8t=6(2t+4)-11 | | 40x^2+190x-50= | | 9-3y-y=1 | | x+3=2(5x-6) | | log[2](x)+log[2](x-4)=3 | | 7x+1=2x-44 |